Nucleoside/Nucleotide Analogues for the Treatment of Chronic Hepatitis B: A 3-Year Follow Up Study - Andri Sanityoso Sulaiman; Irsan Hasan; Cosmas Rinaldi A. Lesmana; Chyntia Olivia M. Jasirwan; Saut Horas H. Nababan; Kemal Fariz Kalista; Gita Aprilicia; Rino Alvani Gani (Jurnal Penyakit Dalam Indonesia)
Introduction. Chronic hepatitis B (CHB) is endemic in Indonesia, where it is usually treated with pegylated interferon and nucleoside/nucleotide analogs (NA). The aim of this study was to determine the efficacy of treating CHB infection among Indonesian patients with NA (lamivudine, telbivudine, and tenofovir) for a 3-year period.